Adipokines from local fat cells shape the macrophage compartment of the creeping fat in Crohn's disease. Issue 6 (28th April 2012) - Kredel, Lea Isabell; Batra, Arvind; Stroh, Thorsten; Kühl, Anja A; Zeitz, Martin; Erben, Ulrike; Siegmund, Britta
Abstract : Objective: The creeping fat in Crohn's disease (CD) is infiltrated by macrophages; local adipokine levels are increased. This study aimed to link these observations to define a role for macrophages in the pathology of human CD. Methods: Human peripheral blood CD14 cells were polarised in vitro into M1 and M2 macrophages. The effects on adipokine receptors, phenotypic surface markers, cytokines and chemokines were assessed after treatment with leptin and adiponectin. Immunohistochemistry visualised macrophage subtypes in samples of mesenteric fat tissue from patients with CD. The chemotactic potential of secreted macrophage products was determined by T cell migration and chemokine production in vitro. Results: Although both adipokines altered the phenotype and function of M1 and M2 macrophages, M2 macrophages were more susceptible. M1 responded to leptin by increased cytokine production, but the stronger effect was seen in M2 macrophages with high expression of interleukin (IL)-10, IL-6 and tumour necrosis factor α. Adiponectin exerted similar effects and led to upregulated mannose receptor expression by M2 macrophages. Large macrophage numbers within the mesenteric fat tissue of patients with CD comprise a unique infiltration predominantly of M2 macrophages, leading to an IL-10-rich environment. While leptin increased the potency of both subtypes to attract CD3 T cells, adiponectin only affected M2 macrophages. Conclusion: The adipocyte-dependent microenvironment within the creeping fat of patients with CD modulates the local macrophage compartment to a preference for the M2 subtype. The findings in this study with human cells suggest a protective role for the mesenteric fat in CD in terms of an enveloping barrier with the potential to limit intestinal inflammation.